Genetic influences on cognitive decline in Parkinson's disease - Morley, J.F. (2012)
BACKGROUND: The role of genetic factors in cognitive decline associated with Parkinson's disease is unclear. We examined whether variations in apolipoprotein E, microtubule-associated protein tau or catechol-O-methytransferase genotypes are associated with cognitive decline in Parkinson's disease. METHODS: We performed a prospective cohort study of 212 patients with a clinical diagnosis of Parkinson's disease. The primary outcome was change in Mattis Dementia Rating Scale version 2 score. Linear mixed-effects models and survival analysis were used to test for associations between genotypes and change in cognitive function over time. RESULTS: The ε4 allele of apoliporotein E was associated with more rapid decline (loss of 2.9 (95% CI, 1.7–4.1) more points/year, p<0.001) in total score and an increased risk of a ≥10 pointdrop during the follow-up period (HR 2.8, 95% CI 1.4–5.4, p=0.003). Microtubule-associated protein tau haplotype and catechol-O-methytransferase genotype were associated with measures of memory and attention, respectively, over the entire followup period but not with the overall rate of cognitive decline. CONCLUSION: These results confirm and extend previously described genetic associations with cognitive decline in Parkinson's disease and imply that individual genes may exert effects on specific cognitive domains or at different disease stages. Carrying at least one apolipoprotein E ε4 allele is associated with more rapid cognitive decline in Parkinson's disease, supporting the idea of a component of shared etiology between Parkinson's disease dementia and Alzheimer disease. Clinically, these results suggest genotyping can provide information about the risk of future cognitive decline for Parkinson's disease patients.